The Methodology Of Feedback System In Evaluating The Formative Assessment In Undergraduate Medical Education Second-Year Pharmacology In A Developing Medical College In Himachal Pradesh: Feedback System In Evaluating - Prashar, Deepak; Loan, Ghulam Mohammad; Kumar, Sanjay; Faller, Erwin M. (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: The aim and objective of the study was to determine the teaching methods and their pros and cons that predominate in students in understanding and scoring in formative and summative assessments. Pharmacology is a course that needs extra care in this direction as this field is ever-changing. It is very difficult for a student to remember the classification of drugs, names, pharmacokinetics Methods: A prospective study was carried out from April 2020 till February 2022. 120 students of second year session 2019, first CBME batch who appeared after 11 months for the summative assessment, were included and there was one drop out case so only 119 students were included Results: pharmacodynamics, indications, contraindications, side effects, and adverse drug reactions. The present study focuses on the mental level and the economical aspects of the persons involved in the establishment of the medical college.